Pengaruh Earning Per Share (Eps), Price Earniing Ratio (Per), Net Profit Margin (Npm), Return On Asset (Roa), dan Return On Equity (Roe) terhadap Return Saham pada Perusahaan Food And Beverage yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2015-2019 - Ajeng Ayu Widi Citra Dewi; Azib Asroi (Bandung Conference Series: Business and Management, 2022)
Abstract. The purpose of this study is to understand how Earning Per Share (EPS), Price Earnings Ratio (PER), Net Profit Margin (NPM), Return On Assets (ROA), and Return On Equity (ROE) may or may not affect stock returns. . The selection approach is purposive sampling, by selecting 12 companies from all food and beverage companies listed on the Indonesia Stock Exchange between 2015 and 2019. The dependent variable of this study is stock returns, while the independent variable is Earning Per Share (EPS), Price Earning Ratio (PER), Net Profit Margin (NPM), Return On Assets (ROA) and Return On Equity (ROE). Multiple linear analysis was conducted to analyze the data in this study. Part of the results of this study indicate partially using the t test that, Price Earning Ratio (PER), Net Profit Margin (NPM), and Return On Assets (ROA) have no significant effect on Stock Return, while Earning Per Share (EPS) and Return On Equity (ROA) has a significant effect on Stock Return. Meanwhile, simultaneously using the F test, it shows that Earning Per Share (EPS), Price Earning Ratio (PER), Net Profit Margin (NPM), Return On Assets (ROA) and Return On Equity (ROE) have no significant effect on Stock Return. Abstrak. Tujuan dari penelitian ini adalah untuk memahami bagaimana Earning Per Share (EPS), Price Earnings Ratio (PER), Net Profit Margin (NPM), Return On Assets (ROA), dan Return On Equity (ROE) mungkin atau tidak berpengaruh terhadap return saham. Pendekatan pemilihannya adalah purposive sampling, dengan memilih 12 perusahaan dari seluruh perusahaan food and beverage yang terdaftar di Bursa Efek Indonesia antara tahun 2015 sampai dengan tahun 2019. Variabel dependen penelitian ini adalah return saham, sedangkan variabel independen nya adalah Earning Per Share (EPS), Price Earning Ratio (PER), Net Profit Margin (NPM), Return On Asset (ROA) dan Return On Equity (ROE). Analisis linier berganda dilakukan untuk menganalisis data dalam penelitian ini. Bagian hasil penelitian ini menunjukkan secara parsial dengan menggunakan uji t bahwa, Price Earning Ratio (PER), Net Profit Margin (NPM), dan Return On Asset (ROA) tidak berpengaruh signifikan terhadap Return Saham, sedangkan Earning Per Share (EPS) dan Return On Equity (ROA) berpengaruh signifikan terhadap Return Saham. Sementara secara simultan dengan menggunakan uji F sekaligus menunjukkan bahwa Earning Per Share (EPS), Price Earning Ratio (PER), Net Profit Margin (NPM), Return On Asset (ROA) dan Return On Equity (ROE) tidak berpengaruh signifikan terhadap Return Saham.